Prevalence of adolescent dual tobacco use and its associated factors: findings from a cross-sectional study - Mohd Firdaus Razali; Mohd Ruhaizie Riyadzi; Hamizatul Akmal Abd Hamid; Khaw Wan-Fei; Ummi Nadiah Yusoff (BMJ Open)
Objective To determine the prevalence and its associated factors of dual tobacco use among Malaysian adolescents in developing effective public health strategies.Design Cross-sectional study.Setting This study analysed data from the National Health and Morbidity Survey (NHMS) 2022: Adolescent Health Survey (AHS), a nationwide cross-sectional survey conducted among secondary school students across Malaysia.Participants This cross-sectional study used data from the NHMS 2022: AHS, which included a representative national sample of Malaysian adolescents between the ages of 13 and 17. Using a two-stage stratified sampling approach, this study included participation from 33 523 adolescents from 240 schools nationwide.Primary and secondary outcome measures The primary outcome was the prevalence of dual tobacco use among Malaysian school-going adolescents aged 13–17, defined as self-reported concurrent use of conventional cigarettes and e-cigarettes in the past 30 days. Secondary outcomes included the factors associated with dual tobacco use, such as sociodemographic characteristics, dual tobacco use behaviour, marital status of parents, tobacco use of parent or guardian, supervision, connectedness, bonding and respect for privacy of parent or guardian, along with peer support and truancy. A complex sample analysis was performed using SPSS V.27.0, maintaining a 95% CI and multiple logistic regression was applied.Results Out of 33 380 Malaysian adolescents surveyed, 1728 (5.5%; 95% CI: 4.88% to 6.28%) reported dual tobacco use. The prevalence was significantly higher among males (9.7%; 95% CI: 8.54% to 10.98%) compared with females (1.4%; 95% CI: 1.15% to 1.70%) and highest among 17 years (8.6%; 95% CI: 7.05% to 10.41%), with a decreasing trend in younger age groups. Predominant vapers constituted the largest proportion (9.9%, 95% CI: 8.66% to 10.13%) among adolescents who reported dual tobacco use, followed by predominant smokers (6.2%, 95% CI: 5.53% to 7.06%), dual daily users (4.5%, 95% CI: 3.18% to 5.64%) and non-daily dual users (3.9%, 95% CI: 2.79% to 4.39%). Dual tobacco use was more prevalent among adolescents whose parents or guardians used tobacco (8.1%; 95% CI: 7.10% to 9.20%). Multiple logistic regression analysis suggested that significant predictors of dual tobacco use included older age (adjusted OR (AOR) for 17 years: 2.92; 95% CI: 2.19 to 3.89), male sex (AOR: 8.53; 95% CI: 6.78 to 10.74), ‘others’ ethnicity (AOR: 1.82; 95% CI: 1.40 to 2.35), predominant vapers (AOR 2.65, 95% CI: 1.96 to 2.72), separated or widowed parental status (AOR: 1.69; 95% CI: 1.42 to 2.02), parental or guardian tobacco use (AOR: 2.47; 95% CI: 2.08 to 2.94), lack of bonding (AOR: 1.79; 95% CI: 1.49 to 2.14), lack of privacy respect (AOR: 1.53; 95% CI: 1.29 to 1.81), lack of peer support (AOR: 1.65; 95% CI: 1.39 to 1.96) and truancy (AOR: 1.81; 95% CI: 1.55 to 2.10).Conclusions This study highlights a concerning prevalence of dual tobacco use (5.5%) among Malaysian adolescents, which is notably higher than the current prevalence of exclusive cigarette smoking (6.2%) and closely approaches that of e-cigarette use (14.9%). Compared with previous national surveys and international benchmarks, the prevalence of dual use among Malaysian youth appears to be rising and represents a significant public health concern. These findings underscore the urgent need for targeted prevention and control strategies addressing both conventional and emerging tobacco products in this population.